2020
DOI: 10.15561/26649837.2020.0506
|View full text |Cite
|
Sign up to set email alerts
|

Differences in kinematic parameters between male and female hammer throw finalists of the World Championship in Daegu in 2011

Abstract: Background and Study Aim. Hammer throwing is the most complex athletic throwing discipline with rotational trajectory and strong effect of several different forces that try to disable the projected throwing trajectory. Kinematic parameters are an important segment in the analysis of athletic disciplines, including hammer throw. They are an indicator of influence and often a difference between competitors of different or the same rank of the competition. The aim of the study was to determine the spatial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 18 publications
4
17
0
2
Order By: Relevance
“…Research by [20] on the sample of finalists of the championship in London shows the existence of differences in kinematic parameters by gender, with isolated ejection height which confirmed the statistical significance, where male finalists throw a hammer from an average height of 1.74 cm height 1.54cm. In the current research, it can be concluded that the height of the ejection followed by the speed of rotation (more than 4.5 m/s) and the ejection speed (higher than 27 m/s) has an impact on the overall result, which is in line with the results of the [21]. The resulting differences between the throwing of the ball and the hammer of male and female finalists can be found in the length of training, different training process, technical mastery, experience of competitors, morphological profile, motor and anatomical structures, technical and biomechanical parameters.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Research by [20] on the sample of finalists of the championship in London shows the existence of differences in kinematic parameters by gender, with isolated ejection height which confirmed the statistical significance, where male finalists throw a hammer from an average height of 1.74 cm height 1.54cm. In the current research, it can be concluded that the height of the ejection followed by the speed of rotation (more than 4.5 m/s) and the ejection speed (higher than 27 m/s) has an impact on the overall result, which is in line with the results of the [21]. The resulting differences between the throwing of the ball and the hammer of male and female finalists can be found in the length of training, different training process, technical mastery, experience of competitors, morphological profile, motor and anatomical structures, technical and biomechanical parameters.…”
Section: Discussionsupporting
confidence: 87%
“…In that case, the neuromuscular coordination and control of the athlete comes to the fore, taking into account the synchronized realization of a large number of kinematic parameters. In general, these parameters differ depending on the gender of the competitors, their motor and technical experience, which is confirmed by the results of the research [17]. Identical conclusions that support the results of this research apply to the so-called long jumps (long, triple jump) which record significant differences in kinematic parameters, and are predictors of good results, and possible differences in running speed on a given section during the run, lengths of the first, second and third step, bounce duration, vertical speed, bounce angle, etc.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations